APLIKASI MODEL WEPP UNTUK PENDUGAAN EROSI DI SUB DAERAH ALIRAN SUNGAI TINALAH - , VINA PRATIWI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Land use conversion caused changes in environmental quality such as increases in erosion and sedimentation. This research aims to determine the magnitude of the erosion predicted by using the WEPP model and to a compare the WEPP model with the USLE model. WEPP (Water Erosion Prediction Project) is the erosion prediction model with the output of soil erosion, sedimentation, and surface run off. The required primary data is soil characteristics such as soil texture, soil depth, albedo, % of sand, % of clay, % of organic matter, the value of Cation Exchange Capacity (CEC), and % of rock. The secondary data needed is climatology data such as daily precipitation, maximum precipitation intensity or average precipitation intensity, maximum daily temperature, minimum daily temperature, daily solar radiation, wind speed, dew point temperature, astronomical of rainfall station, elevation of rainfall station, contour map, soil map, and land use map. The erosion prediction analysis is carried out by using the method of WEPP and USLE models. The average ratio test (T-Test) was used to compare the both of erosion prediction models. The conclusion drawn in this research showed that the result of erosion prediction of WEPP model was 39.15 tons/ha/yr and the USLE model was 505.51 tons/ha/yr. Tinalah Sub Watershed erosion allowable limits was exceeded 12.63 tons/ha/yr. The results of Comparative analysis test of two models indicated that the predicted erosion of WEPP model and USLE model significantly different.